Conocimiento materno y grado de desarrollo del lenguaje en preescolares, Victor Larco 2014 - García Espinoza, Joana del Pilar (2015)
This research study is descriptive - correlational cross-sectional and performed in the I.E.I. N° 224 "Indoamerica" in the District of Victor Larco, in order to establish the relationship between the level of maternal knowledge of language stimulation and the degree of psychomotor development in the area of language in preschool. The sample consisted of 50 mothers and preschoolers. To collect data two instruments were used: Psychomotor Development Test - Subarea Language (TEPSI-SAL); Test and Measuring Knowledge Level Language Stimulation (TEMNCEL). The analysis of the relationship between the study variables was performed by Test of Independence (Chi square test with Yates correction) found no relationship between the level of maternal knowledge of language stimulation and the degree of psychomotor development in the area of language in preschool. Keywords: Maternal Knowledge, Development Degree in the area of language presc